Хөөрөгний тухай өгүүлэхүй - Ариун-Эрдэнэ, Х. (Historia Mongolarum, 2003)
The article deals with snuff bottles and its traditions, especially the rarest examples, most presious examples. The origin, development and traditions are discussed.